Analisis Kerusakan Jalan dengan Metode PCI Untuk Jalan Jati Kota Palangka Raya - Fadillah, Haris; Murniati, Murniati; Robby, Robby (Universitas Batanghari Jambi, 2024)
A fully functional road facilitates the movement of people from one place to another, yet road damage can pose threats to the safety and comfort of users. Jati Road serves as a secondary collector road connecting residential centers. The density of traffic on this route is high due to the presence of residential areas and schools nearby. Damage to Jati Road can have a negative impact on the road users' experience. This research aims to determine the types and levels of damage using the PCI method. The study was conducted directly on Jati Road by dividing it into several sections, each spanning 100 meters. Each segment was then visually inspected and measured to identify any damage. The research findings indicate that the PCI of Jati Road in Palangka Raya City reached 73.19%, which is considered very good.